Determination of Bacterial Species Associated with Contamination of Poultry Feeds Produced by Three Different Companies in Abuja, Nigeria - Gloria G Ezeagu; Maryam Bukar; Morenike Fadayomi (UMYU Journal of Microbiology Research)
Poultry farming is an efficient source of income and nutrition.  Feeds used for poultry are vulnerable to contamination by microorganisms.  This study aimed to assess bacterial contaminants of the poultry produced from three different companies in Abuja, Nigeria.  Samples of poultry feeds produced by three different companies were collected from three different batches and were processed and inoculated in nutrient agar, Eosin methylene blue agar (EMB), and Mannitol salt agar (MSA), incubated at 37 °C for 24 hours.  Colonies were counted, characterized, and subcultured to obtain pure cultures.  Pure isolates were identified using Gram reaction, cellular morphology, and biochemical characteristics. Antibiotic susceptibility profiles of the isolated bacterial species were determined using Kirby-Bauer disc diffusion. The total bacterial counts of samples analyzed showed that poultry feed from sample C had the highest mean bacterial counts of 2.49 x 105CFU/g.  The lowest was poultry feed sample A, with a mean count of 1.06 x 105CFU/g.  Sample B had a mean bacterial count of 2.14 x 105CFU/g.  The bacterial species isolated in the present study are Staphylococcus aureus, Escherichia coli, Salmonella sp., and Proteus mirabilis.  Staphylococcus aureus was the most occurring isolate with a 47% occurrence rate and was present in all poultry feed samples.  Escherichia coli is the second most occurring with a 35% occurrence rate, then Salmonella with a 10% occurrence rate.  The least occurring was Proteus mirabilis, with an 8% occurrence rate.  S. aureus showed 100% susceptibility to all the antibiotics used, while P.  mirabilis recorded the highest resistance of 40 %, showing resistance to four of the ten antibiotics used.  This study reveals the presence and high microbial count in the different poultry feeds investigated.  This usually reflects the degree of hygienic procedures and biosecurity used in the feeds' handling, production, and storage.